2004
DOI: 10.1590/s0041-87812004000500002
|View full text |Cite
|
Sign up to set email alerts
|

Low coronary perfusion pressure is associated with endocardial fibrosis in a rat model of volume overload cardiac hypertrophy

Abstract: Coronary driving pressure falls and ventricular pressures increase early after aortocaval fistula and are associated with subsequent myocardial fibrosis deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…Collagen deposition and its removal by matrix metalloproteinases (MMPs) are regulated by focal adhesion kinase (FAK) (19), which is dynamically regulated by mechanical stress and inflammation. We previously demonstrated that silencing FAK in endotoxemic rats protected against the development of cardiac dysfunction and remodeling (11). In addition, myocardial MMP activation induced chamber dilatation and ventricular dysfunction (20).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Collagen deposition and its removal by matrix metalloproteinases (MMPs) are regulated by focal adhesion kinase (FAK) (19), which is dynamically regulated by mechanical stress and inflammation. We previously demonstrated that silencing FAK in endotoxemic rats protected against the development of cardiac dysfunction and remodeling (11). In addition, myocardial MMP activation induced chamber dilatation and ventricular dysfunction (20).…”
Section: Introductionmentioning
confidence: 97%
“…Septic shock causes a reduction in diastolic arterial pressure (DAP) and, consequently, a reduction in coronary driving pressure (CDP), which is important for maintaining myocardial perfusion (11). The CDP is the difference between DAP and left ventricular end-diastolic pressure (LVEDP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GUIDO MC et al 1 point out that left ventricular hypertrophy following volume overload is regarded as an example of cardiac remodeling without increased fibrosis accumulation. Infarction is associated with increased fibrosis within the noninfarcted, hypertrophied myocardium, particularly in the subendocardial regions.…”
mentioning
confidence: 99%
“…Estudos demonstram que o IAM está associado com uma abundante perda de miocárdio que é substituída por uma cicatriz a base de colágeno (Guido et al, 2004;Frangogiannis, 2014 (Goldman et al, 1995;Francis et al, 2001;Savergnini et al, 2013). …”
unclassified